Cardiac transplantation in transthyretin amyloid cardiomyopathy: Outcomes from three decades of tertiary center experience - Razvi, Yousuf; Porcari, Aldostefano; Di Nora, Concetta; Patel, Rishi K.; Ioannou, Adam; Rauf, Muhammad U.; Masi, Ambra; Law, Steven; Chacko, Liza; Rezk, Tamer; Ravichandran, Sriram; Gilbertson, Janet; et al. (Frontiers in Cardiovascular Medicine, 2023)
Aims Transthyretin cardiac amyloidosis (ATTR-CM) is a progressive and fatal cardiomyopathy. Treatment options in patients with advanced ATTR-CM are limited to cardiac transplantation (CT). Despite case series demonstrating comparable outcomes with CT between patients with ATTR-CM and non-amyloid cardiomyopathies, ATTR-CM is considered to be a contraindication to CT in some centers, partly due to a perceived risk of amyloid recurrence in the allograft. We report long-term outcomes of CT in ATTR-CM at two tertiary centers. Materials and methods and Results We retrospectively evaluated ATTR-CM patients across two tertiary centers who underwent transplantation between 1990 and 2020. Pre-transplantation characteristics were determined and outcomes were compared with a cohort of non-transplanted ATTR-CM patients. Fourteen (12 male, 2 female) patients with ATTR-CM underwent CT including 11 with wild-type ATTR-CM and 3 with variant ATTR-CM (ATTRv). Median age at CT was 62 years and median follow up post-CT was 66 months. One, three, and five-year survival was 100, 92, and 90%, respectively and the longest surviving patient was Censored > 19 years post CT. No patients had recurrence of amyloid in the cardiac allograft. Four patients died, including one with ATTRv-CM from complications of leptomeningeal amyloidosis. Survival among the cohort of patients who underwent CT was significantly prolonged compared to UK patients with ATTR-CM generally (p < 0.001) including those diagnosed under age 65 years (p = 0.008) or with early stage cardiomyopathy (p < 0.001). Conclusion CT is well-tolerated, restores functional capacity and improves prognosis in ATTR-CM. The risk of amyloid recurrence in the cardiac allograft appears to be low.